(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article provides detailed information about the methodology of using interactive methods in teaching genetics. In particular, the features of teaching genetics that are important for teachers today, modernization of the organization of the educational process of professors and teachers working in higher education institutions, pedagogical work in higher education institutions modernization of the organization of the educational process of professors and teachers, the use of passive methods, active methods, and interactive methods in teaching genetics.